A male infant with Xq22.2q22.3 duplication containing PLP1 and MID2. Issue 3 (17th January 2020) - Chanchani, Swati R.; Xie, Hongyan; Sekhon, Gurbax; Melikishvili, Ana M.; Moyer Harasink, Sue; Pall, Harpreet; Giampietro, Philip F.
Abstract: Background: The Xq22.2 q23 is a complex genomic region which includes the genes MID2 and PLP1 associated with FG syndrome 5 and Pelizaeus–Merzbacher disease, respectively. There is limited information regarding the clinical outcomes observed in patients with deletions within this region. Methods: We report on a male infant with intrauterine growth retardation (IUGR) who developed head titubation and spasticity during his postnatal hospital course. Results: Chromosome microarray revealed a 6.7 Mb interstitial duplication of Xq22.2q22.3. Fluorescence in situ hybridization showed that the patient's mother also possessed the identical duplication in the Xq22.3q22.3 region. Among the 34 OMIM genes in this interval, the duplication of the PLP1 (OMIM# 300401) and MID2 (OMIM# 300204) appears to be the most significant contributors to the patient's clinical features. Mutations and duplications of PLP1 are associated with X‐linked recessive Pelizaeus–Merzbacher disease (PMD). A single case of a Xq22.3 duplication including the MID2 has been reported in boy with features of FG syndrome. However, our patient's clinical features are not consistent with the FG syndrome phenotype. Conclusion: Our patient's clinical features appear to be influenced by the PLP1 duplication but the clinical effect of other dosage sensitive genes influencing brain development cannot be ruled out. Abstract : A male infant with head titubation, pendular nystagmus, and spasticity was identified as having an Xq22.2Xq22.3 chromosome microdeletion on chromosome microarray. The deletion contains the PLP1 and MID2 OMIM genes. The patient's phenotypic features appear consistent with Pelizaeus–Merzbacher disease.